Modelling and operation performance of the hybrid borehole heat exchangers constituted of a shallow U-pipe array and medium-deep coaxial pipe - Shilong Yang; Yaru Li; Lingfeng Huang; Qingbo Yang; Ke Zhu; Yudong Mao; Wenke Zhang; Mingzhi Yu (Energy and Buildings, 2026)

An incoherent feed-forward loop coordinates nitrate uptake and tillering in wheat - Weiya Xu; Yongming Chen; Yanxiao Niu; Bin Liu; Dejie Du; Xining Ning; Tong Huan; Yilan Zhou; Wensheng Ke; Lingfeng Miao; Weilong Guo; Mingming Xin; et al. (Molecular Plant, 2025)

Adaptation of Marine Heterotrophic Protists to Long‐Term Warming Selection - Mengwen Pang; Zuyuan Gao; Lingfeng Huang; Chuk Man Chan; Xiaodong Zhang; Ruilin Su; Ke Pan; Hongbin Liu (Global Change Biology, 2025)
The rise in surface ocean temperature imposes strong effects on marine organisms. With large population sizes and fast generation times, microorganisms may rapidly adapt to ocean warming. However, long‐term experimental adaptation studies on heterotrophic protists are very limited, hindering our comprehensive understanding of their adaptation capability and the underlying mechanisms. In this study, we conducted long‐term thermal selection experiments on six representative marine protozoa. By assessing their phenotypes, metabolism, thermal performance curves, thermal traits, and carbon allocation status, we found that all investigated heterotrophic protists exhibited a fitness‐improved adaptation response to warming scenarios. After growing in warmer conditions for hundreds of generations (~850 for Cafeteria burkhardae and ~500 for other species), their optimal temperature and maximum rates of both growth and ingestion increased, whereas respiration rates significantly decreased. In addition, the cell size, cellular carbon, and nitrogen content at an elevated environmental temperature also increased after warming adaptation. Mechanisms underlying the increased competitive fitness at high temperatures after warming adaptation might be associated with the alleviated oxidative stress, shown by the remarkable reduction in cellular reactive oxygen species contents. Our study, for the first time, reveals the ability of marine heterotrophic protists to adapt to higher temperatures, providing experimental support for predictive modeling studies that integrate evolutionary potential with short‐term physiological responses, with important implications for marine ecosystem functioning and biogeochemical cycling under global warming.

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Quenching-induced surface reconstruction of perovskite oxide for rapid and durable oxygen catalysise - Lingfeng Ke; Shengli Pang; Chao Long; Ting Fang; Gongmei Yang; Yifan Song; Xudong He; Shuai Ma; Yaozheng Qian; Xiangqian Shen; Chonglin Chen (Chemical Engineering Journal, 2023)

Gametogenic cycle and biochemical composition of the clam Mactra chinensis (Mollusca: Bivalvia): Implications for aquaculture and wild stock management - Qi Li; Lin Yang; Qiaozhen Ke; Lingfeng Kong (Marine Biology Research, 2011)